Buddhist Landscapes in Central India: Sanchi Hill and Archaeologies of Religious and Social Change, c. Third Century BC to Fifth Century AD - Shaw, Julia (UNIV COL LONDON INST ARCH PUB, 2013)
The "monumental bias" of Buddhist archaeology has hampered our understanding of the socio-religious mechanisms that enabled early Buddhist monks to establish themselves in new areas. To articulate these relationships, Shaw presents here the first integrated study of settlement archaeology and Buddhist history, carried out in the area around Sanchi, a Central Indian UNESCO World Heritage site. Her comprehensive, data-rich, and heavily illustrated work provides an archaeological basis for assessing theories regarding the dialectical relationship between Buddhism and surrounding lay popul